A PRELIMINARY STUDY ON THE GROWTH AND FOOD OF STOLEPHORUS SPP. FROM THE JAKARTA BAY - Burhanuddin, -; Martosewojo, Sularto; Hutomo, Malikusworo (Marine Research in Indonesia, 1975)
The length compositions of Stolephorus heterolobus, Stolephorus insularis and Stolephorus  pseudoheterolobus  were observed. S. heterolobus ranged from 25 to 71 mm., S. insularis from 27 to 75 mm and S. pseudoheterolobus from 27 to 67 mm standard length. The  ages  of these  three  species  were estimated. The  asymptotic  length  of S. heterolobus was 97 mm attained at the age of 26 months, S. insularis 86 mm at 26 months and S. pseudohetorolobus 88 mm at 20 months. The highest growth rate of S. heterolobus was at the size group 30 - 80 mm standard length, that of S. insularis was at 30-50  mm, and that of S. insularis was observed to be the lowest. The stomach contents of S. heterolobus and S. pseudoheterolobus   were studied tand were found that the food  of these two  species  was  more or  less the  same. They fed mainly on zooplankton consisting of copepods and other crustaceans.